Hypoxia-induced tRF-3Thr-CGT promotes hepatocellular carcinoma progression via mitochondrial energy metabolism remodeling dependent on the mtDNA-translation mechanism - Qu, Xianzhi; Liu, Buhan; Jin, Duo; Ma, Yue; Liu, Mingjun; Yan, Xiaoyu; Su, Jing; Zhou, Lei (Frontiers in Pharmacology, 2025)
Hypoxia is one of the major characteristics of the tumor microenvironment, and it promotes mitochondrial energy metabolic remodeling for hepatocellular carcinoma (HCC) progression. It is believed that under dual control of the mitochondrial genome (mtDNA) and the nuclear genome (nDNA) mitochondria coordinate multiple signals to alter energy metabolism under hypoxic stress. Currently, it has been found that hypoxia promotes tRNA cleavage to produce tRFs (tRNA-derived fragment), which have attracted attention as potential biomarkers and therapeutic targets. In this study, we found that hypoxic stress could drive HCC cell invasion and migration. Furthermore, the expression of core oxidative phosphorylation (OXPHOS) proteins encoded by nDNA and mtDNA were uncoordinated under hypoxia. Therefore, the human mitochondrial peptide deformylase (HsPDF) which was essential for mtDNA-encoded protein translation and respiratory chain maintenance has been brought into focus. We found that hypoxic stress significantly suppressed HsPDF which was responsible for mtDNA-encoded protein inhibition. To further explore the possible mechanism, high-throughput sequencing was used to map tRF expression patterns in HCC cells under hypoxia. We found that hypoxic stress altered their subtype distributions and that the high expression of tRF-3Thr-CGT, which has functions in transcription and translation regulation, may potentially bind to the 3ʹ-UTR of HsPDF. Upregulated tRF-3Thr-CGT could inhibit HsPDF and mitochondrial OXPHOS function. Furthermore, the orthotopic liver cancer model in mice also indicated that the tRF-3Thr-CGT inhibitor significantly suppressed tumor progression. These results collectively suggested that tRFs may have roles in mitochondrial protein coordination and become novel pharmacological targets for mitochondrial remodeling under tumor microenvironment remodeling of HCC therapy.